A Technology For Developing Cognitive Flexibility In Primary School Students Using Generative AI - Yuliya Vasilyevna Rysyukova (Zien Journals, 2026)
This article describes the main characteristics of the "4K" model, as well as the technology for the formation and development of cognitive flexibility, communication skills and critical thinking in the school education system.
Keywords: communication; creative thinking; critical thinking; collaboration